AN ANALYSIS ON STUDENTS' ABILITY AND DIFFICULTY IN WRITING NARRATIVE TEXT: A Research Study Concerning on Writing Skill of Eleventh Grade Student - Diniya, Tabah Ghifary (2013)
The research paper entitled "An Analysis on Students' Ability and Difficulty in Writing Narrative Text" attempted to investigate what are the students' ability and difficulties in writing narrative text as a "natural" text genre. This study is also focused on revealing what kinds of processes and circumstances that students use in their narrative seen from the transitivity system. This study was conducted in one public senior high school in Purwakarta. This study used a case study research design. The data were thirty five students' works which are categorized into three different levels of achievement that are low, middle, and high achievers. The texts were analyzed using the Rose's Scoring System (2007), Halliday(1985, 1994), Gerot and Wignell (1994),Levine (1993), Richard (1974), Knapp and Watkins (2005). The findings of this study show that the students' errors on their writing are verb pattern error, sentence sprawl, and punctuation. These errors are mainly caused by over-generalization and ignorance of rule restriction that students do. Material and mental processes are spotted to be the most appearing processes in the students' works, whereas the occurrences of circumstances tend to be equal. Keywords: Students' Error, Narrative text, Transitivity system Penelitian yang berjudul "Analisis pada Kemampuan dan Kesulitan Siswa dalam Menullis Teks Naratif" ini bertujuan untuk mengetahui sejauh mana kemampuan siswa dan apa saja kesulitan yang dialami siswa dalam menulis teks naratif sebagai jenis teks yang "natural". Penelitian ini juga berfokus untuk mengungkapkan jenis processes dan circumstances apa saja yang digunakan siswa didalam teksnya ditinjau dari sistem transitivity. Penelitian ini dilaksanakan di sebuah sekolah menengah atas negeri di Purwakarta. Penelitian ini menggunakan metode study kasus. Data yang diambil merupakan 30 tulisan siswa yang kemudian dikategorikan menjadi tiga kelompok pencapaian, yaitu, rendah, sedang dan tinggi. Hasil kerja siswa tersebut kemudian dianalisis dengan teori-teori dari Rose's Scoring System (2007), Halliday(1985, 1994), Gerot and Wignell (1994),Levine (1993), Richard (1974), Knapp dan Watkins (2005). Hasil penelitian menunjukan bahwa kesalahan sisawa bersumber dari verb pattern error, sentence sprawl, dan punctuation. Kesalahan-kesalahan ini terjadi disebabkan oleh over-generalization dan ignorance of rule restriction yang dilakukan siswa. Kata kunci: Students' Error, Narrative text, Transitivity system